IEEE 802.16: WiMAX overview, WiMAX architecture - Seyedzadegan, Mojtaba; Othman, Mohamed (International Association of Computer Science and Information Technology, 2013)
WiMax, the Worldwide Interoperability for Microwave Access is a new technology dealing with provision of data over long distance using wireless communication method in many different ways. Based on IEEE 802.16 WiMax is claimed as an alternative broadband rather than cable and DSL. This paper is a quick technical overview and covers:WiMAX overview(Fundamental Concept; Technology; Standard update) andWiMAX architecture(Network and Node Architectures; Physical Layer; MAC Layer).